Implementation Of Pedagogical Technologies in The Lessons of Mathematics for The Development Of Thinking In Students Of Elementary Classes In The Republic Of Uzbekistan - Svetlana Saylaubaevna Saitbekova (Genius Journals, 2022)
In Uzbekistan, from the first years of independence, attention was paid to the issue of reforming the educational system at the level of State policy, priority is given to our children getting education at the level of world standards, their physical and spiritual development, the realization of abilities and talents, the formation of feelings of devotion to Homeland and dedication
Keywords: primary education; innovation; pedagogical technologies; imaginative thinking